ANALISIS TINGKAT KEBUTUHAN MODAL KERJA PADA BMT MANDIRI ABADI SYARIAH DI KOTA MEDAN - Prastiwi Nomi (STAI Syekh.H. Abdul Halim Hasan Al Ishlahiyah Binjai, 2022)
The purpose of this study was to analyze the working capital of BMT in meeting the needs of the BMT Mandiri Abadi Syariah cooperative. to analyze BMT Mandiri Abadi Syariah in collecting funds from the public. to analyze what are the obstacles faced by BMT Mandiri Abadi Syariah in collecting funds from the public. This study uses a qualitative approach. The results of the research show that the collection of funds by BMT is obtained through savings, namely funds entrusted by customers to BMT to be channeled to the productive sector in the form of financing. These deposits can be in the form of wadi'ah savings, short-term and long-term mudharabah deposits. The strategy used in raising funds at BMT Mandiri Abadi Syariah is a pick-up and promotion system strategy. and optimal socialization in society. The things that become obstacles in meeting the capital requirements at BMT Mandiri Abadi Syariah are the existence of problematic financing such as customers who fail to pay and the weakness of management in analyzing a decision related to the feasibility of financing given not because of consideration but feelings.